电废循环—面向新能源汽车电池中有色金属的电磁涡流分选技术 - Xu, Zheng; Zhao, Kai; Bao, Pengchao (БНТУ, 2023)
At present, the new energy power battery is about to enter the decommissioning climax, sorting metal is one of the important step, this paper describes our optimization and innovation of the traditional waste power battery process. The research and development of the new vertical eddy current sorter breaks through the bottleneck of the original equipment, and realizes a breakthrough for the problem of not being able to deal with small-sized electronic waste (original eddy current sorting equipment), the problem of only being able to separate non-metals and metals, not being able to separate different metals at the same time (high-voltage electrostatic equipment), and the problem of highpollution and high-emission (chemical treatment), focusing on the solution of the recovery of the metal with a particle size of less than 5mm. The Recycling Process is a mechanical-physical device that realizes the separation of small-sized nonmetals from metals and between different metals. Based on this, on the traditional recycling process, we also added two processes of freezing crushing and wind selection, freezing crushing by controlling the temperature, the use of which solid waste at low temperatures in the brittle fracture temperature difference, so that the material becomes brittle, in addition to the crushing effect is better, the advantages of energy saving and noise reduction are also very obvious, the wind selection to a certain extent to make the degree of dissociation of the waste power batteries is higher, so that the separation of metal and non-metallic materials more thoroughly, thus improving the recycling efficiency. It also improves the recycling efficiency.